Role of Bima in the Reputation Management of the Pandawas in the Wayang Play "Babad Alas Wanamarta" (Jejer Scene): A Roland Barthes Semiotic Analysis - Muhammad Asnan; Bimantoro, Ignatius; Sukma, Ferry Indra (International Journal of Multidisciplinary Applied and Science Research, 2025)
This study aims to analyze the role of the character Bima in the reputation management of the Pandawas in the wayang play "Babad Alas Wanamarta" (Jejer scene) using Roland Barthes' semiotic approach. The research focuses on how Bima's actions, speech, and displayed symbols contribute to building, restoring, and maintaining a positive image of the Pandawas amidst a reputational crisis engineered by Patih Sengkuni and the Kurawas. Data was obtained through textual and scene analysis of the wayang play version by Ki Dalang Seno Nugroho, focusing on four reputational crisis scenes, two Pandawa response scenes, and three public perception scenes. Analysis was conducted at three levels: denotation (literal meaning), connotation (cultural meaning), and myth (ideological belief). The results show that Bima acts as a reputational actor who uses firm yet polite communication strategies, exemplary attitude ("nrimo ing pandum"), and value consistency to improve the Pandawas' image. These findings confirm that in the context of traditional public relations, reputation management is carried out not only through active campaigns but also through symbolic representation, steadfast character, and stakeholder perception management. This research concludes that Barthes' semiotic analysis can reveal the dimension of symbolic communication in wayang as a form of early PR, as well as its relevance to modern identity, image, and reputation management theories.